Intravitreal Anti-Vascular Endothelial Growth Factor Therapies for Retinal Disorders - Abraham Hang; Samuel Feldman; Aana P. Amin; Jorge A. Rivas Ochoa; Susanna S. Park (MDPI AG, 2023)
Vascular endothelial growth factors (VEGFs) are key mediator of retinal and choroidal neovascularization as well as retinal vascular leakage leading to macular edema. As such, VEGF plays an important role in mediating visually significant complications associated with common retinal disorders such as diabetic retinopathy, retinal vein occlusion, and age-related macular degeneration. Various drugs that inhibit vascular endothelial growth factors (anti-VEGF therapies) have been developed to minimize vision loss associated with these disorders. These drugs are injected into the vitreous cavity in a clinic setting at regular intervals. This article provides an overview of the various anti-VEGF drugs used in ophthalmology and the common retinal conditions that benefit from this therapy.